Evaluation of Serum Level of Cystatin C and Fetuin A in Patients with Chronic Renal Failure - Marwa Nabeel Hameed; Khudhair A. Khudhair; Yasir I. abbas (Institute of Medico-legal Publications Pvt Ltd, 2021)
The study found that, serum fetuin-A was significantly reduced in CKD patients before dialysis (19.07±4.24 ng/ml) as compared with healthy individuals (22.5±5.94 ng/ml), P<0.01 and in CKD patients after dialysis (19.74±4.25 ng/ml) as compared with healthy individuals. The study found that, serum cystatin C was significantly reduced in CKD patients before dialysis (12.95±1.54 ng/ml) as compared with healthy individuals (8.16±2.37 ng/ml), P<0.01 and in CKD patients after dialysis (12.39±1.66 ng/ml) as compared with healthy individuals. The study showed a significant negative correlation between CKD patients before dialysis and after dialysis regarding cystatine C (r: -0.37). The study found that, blood urea was significantly increased in CKD patients before dialysis (164.3±30.1 mg/dl) as compared with healthy individuals (24.9±3.7 mg/dl), P<0.01 and in CKD patients after (76.1±29.2 mg/dl) as compared with healthy individuals and there was a significant difference in B. urea between CKD patients before and after dialysis (P<0.01). The study also indicated that S. creatinine was significantly increased in CKD patients before dialysis (5.61±1.99 mg/dl) followed by patients after dialysis (3.43±1.47 mg/dl) as compared with healthy individuals (0.57±0.24 mg/dl) (P<0.01). The study showed a significant negative correlation between of Fetuin-A level with B. urea, S. creatinine and S. cysteine in CKD patients before dialysis and after dialysis